A career path framework for teaching focused faculty in graduate health professions and human services education - Canares, Glenn; Riley, Scott Jamieson; Gordes, Karen L. (Frontiers in Education, 2025)
Over the past few decades, the composition of university faculty has shifted from full-time tenure to contingent positions. Despite this change, the Appointments, Promotion and Tenure (APT) process has not evolved with this shift. Contingent faculty may lack university-supported mentoring and professional development, leading to growing dissatisfaction and higher turnover. This turnover affects education quality and campus stability. To retain contingent faculty, with a focus on teaching-focused faculty (TFF), and to foster strong communities, universities should consider new development and promotion pathways for TFF. We describe an updated promotion pathway as a potential solution.